nD control systems in a practical sense - Xu, Li; Saito, Osami; Abe, Kenichi (Zielona Góra: Uniwersytet Zielonogórski)
In view of the features of practical nD signals and systems, this paper presents a comprehensive treatment on some theoretical and methodological results and possible applications for the control of nD systems in the practical sense that the input and output signals of the systems are unbounded in, at most, one dimension.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka